Exploring the relationship between strategic leadership, quality culture and performance in international schools in Malaysia - Eslami, Fakhriyeh (Kulliyyah of Education, International Islamic University Malaysia, 2016)
This study explores the relationship among strategic leadership, quality culture and performance among teachersat three international schools in Malaysia. The study used a survey method and data were collected using adapted questionnaires with six-pointLikert scale. It measured the strategic leadership, quality culture and teacher performance. 145 teachers were sampled to collect data. The data were analysed using descriptive statistics, simple regression analysis, Pearson correlation, independent t-test and ANOVA. Strategic leadership is confined to the original nine point model of strategic leadership (five organizational abilities and four individual characteristics of strategic leadership) by Davies (2004); Davies and Davies (2006); the construct of quality culture is represented by nine distinct factors by Johnson (2000). Finding from descriptive analysis of the study discovered that the school leaders in three international schools in Malaysia possessed all the nine dimensions of strategic leadership. It also indicated that all nine factors of quality culture were implemented by the school leaders. The result of simple regression analysis represented that there was a statistically significant influenceof strategic leadership, quality culture on performance amongteacher in three international schools in Malaysia. Result of Pearson correlation analysis showed that quality culture has significant relationship with organizational capability and individual characteristics. However, this study indicated that there was no significant difference between demographical characteristics in performance among teachers in three international schools in Malaysia. Thus, this study highlighted implementing operative leadership styles such as strategic leadership are vital to deal with both the need for improving performance and the need for the change through quality culture.As the implications of this study, the findings also suggested that management, educational programme designer's educational, supervisors and most importantly quality managers wouldbe aware of effective strategies and quality programmes that can revitalize the quality management associated with teachers in schools.